Effect of COVID-19 pandemic on the workflow of endoscopy units: an international survey. (April 2021) - Resál, Tamás; Bor, Renáta; Szántó, Kata; Fábián, Anna; Rutka, Mariann; Sacco, Marco; Ribaldone, Davide Guiseppe; Molander, Pauliina; Nancey, Stephane; Kopylov, Uri; Vavricka, Stephan; Drobne, David; et al.
Introduction: The coronavirus disease 2019 (COVID-19) pandemic poses a challenge to healthcare. Staff and patients are at increased risk during an examination or intervention, so certain restrictions ought to be introduced. Hence, we aimed to measure the effect of the pandemic on endoscopy units in real-life settings. Methods: This was an observational, cross-sectional, questionnaire-based study, carried out between 7 April and 15 June 2020. Responds came from many countries, and the participation was voluntary. The survey contained 40 questions, which evaluated the effect of the COVID-19 pandemic on the endoscopy units and assessed the infection control. Results: A total of 312 questionnaires were filled, 120 from Hungary, and 192 internationally, and 54 questionnaires (17.3%) were sent from high-risk countries; 84.9% of the gastroenterologists declared that they read the European Society of Gastrointestinal Endoscopy (ESGE) statement, while only 32.1% participated in any advanced training at their workplace. Overall, 92.1% of gastroenterologists realized risk stratification, and 72.1% claimed to have enough protective equipment. In 52.6% of the endoscopy units, at least one endoscopist had to discontinue the work due to any risk factor, while 40.6% reported that the reduced staff did not affect the workflow. Gastroenterologists considered that the five most important examinations both in low and high-risk patients are the following: lower/upper gastrointestinal (GI) bleeding with hemodynamic instability, endoscopic retrograde cholangiopancreatography (ERCP) in obstructive jaundice, foreign body in the esophagus, ERCP in acute biliary pancreatitis, and iron deficiency anemia with hemodynamic instability, which correlates well with the ESGE recommendation. Significant correlation was found in the usage of the necessary protective equipment in high-risk patients depending on the countries ( p  < 0.001). Conclusions: The survey found weak correlation in preliminary training depending on countries; nevertheless, in Hungary during the examined period, endoscopists considered the recommendations more strictly than in other countries. Although many physicians left the endoscopy lab, the workflow was not affected, probably due to the reduced number of examinations.